1999
DOI: 10.1063/1.870069
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional stability of a vortex pair

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
56
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 33 publications
9
56
0
Order By: Relevance
“…5 (b),(g) and (c),(h) respectively, we can see similar structure in the vorticity fields. Additionally, the anti-symmetric structure of the perturbation can be observed in the dominant eigenmodes in all cases, as found by [22,17]. Fig.…”
Section: Structuresupporting
confidence: 52%
See 3 more Smart Citations
“…5 (b),(g) and (c),(h) respectively, we can see similar structure in the vorticity fields. Additionally, the anti-symmetric structure of the perturbation can be observed in the dominant eigenmodes in all cases, as found by [22,17]. Fig.…”
Section: Structuresupporting
confidence: 52%
“…Continuing to even smaller vertical scales, viscous effects increase and may damp out the instability, and hence the growth rate decays with increasing k z F h in the limit of large k z F h . Oscillatory growth rates are observed for the smallest k z F h as observed in [22]. The imaginary part of the growth rate σ i remains zero everywhere else except in a small region surrounding the local minimum between the zigzag and short-wave peaks.…”
Section: Numerical Schemementioning
confidence: 64%
See 2 more Smart Citations
“…In the context of aeronautics, the will to reduce the aircraft wake and the associated hazards to forthcoming planes has motivated the study of the stability of columnar vortices. Since the early works of Crow (1970), Moore & Saffman (1975) and Tsai & Widnall (1976), many studies have shown the sensitivity of the wing-tip vortex pair to both long-and short-wave cooperative instabilities, see Leweke & Williamson (1998) or Billant et al (1999) amongst others. Conversely, a single vortex is asymptotically stable but it supports various families of oscillating and damped modes amongst which are the so-called Kelvin waves (Fabre et al 2006).…”
Section: Introductionmentioning
confidence: 99%